Molecular simulation of mechanical properties of CoCrFeMnNi high-entropy alloy under tension and compression - Tan, Byron Zikang (Nanyang Technological University, 2023)
This Final Year Project report presents the mechanical properties of CoCrFeMnNi high-entropy alloy. This will be done by subjecting the high-entropy alloy to tensile and compression load at different grain sizes to determine the effects of strain rate on the mechanical responses and the mechanism underlying the plastic deformation.